Characterization of the novel HLA‐A*11:383N and HLA‐A*11:388N alleles by next‐generation sequencing. (28th December 2021) - You, Xuan; Wang, Jielin; He, Yanmin; He, Ji; Zhu, Faming
Abstract : Compared with HLA‐A*11:01:01:01, the alleles HLA‐A*11:383N, and HLA‐A*11:388N each show one single nucleotide substitution.